Silver nanoparticle biogenically synthesized by Psychotria malayana Jack and its antimicrobial and cytotoxic activities - Muhammad Taher; Nur Afifah Mohd Zulkafly; Deny Susanti; Tengku Karmila Tengku Mohd Kamil (IIUM Press, International Islamic University Malaysia, 2023)
Introduction: Attributable to antimicrobial and cytotoxic properties of nanoparticles, their use is believed to be able to combat antimicrobial resistance and chemoresistance. In synthesizing nanoparticles, green synthesis method is widely studied because it is environmental-friendly due to use of biological agents as reducing and stabilising agents. Psychotria malayana Jack is rich with phytochemicals possessing many potential bioactivities. Thus, this study aims to extract phytochemicals from leaves of P. malayana Jack and to biogenically synthesise silver nanoparticles (AgNPs-PM) using the extract. Methods: The leaves of P. malayana Jack was extracted in methanol-water solvent via ultrasound assisted extraction and it was incubated in silver nitrate solution for 24 hours. The formation of AgNPs-PM was confirmed via UV-Visible, scanning electron microscopy, zeta particle size and zeta potential analysis. The synthesized AgNPs-PM were tested for their cytotoxicity on human colorectal adenocarcinoma cells (CaCO-2) and human epithelial breast adenocarcinoma cells (MCF-7) via 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide (MTT) colorimetric assay. For antimicrobial activity, they were tested on Bacillus subtilis, Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus using disc diffusion method. Results: AgNPs-PM were successfully synthesized using P. malayana Jack extract as reducing and stabilising agents. Liquid chromatography mass spectrometry analysis showed that flavonoids, amino acids and heterocyclic compounds are among phytochemicals of P. malayana Jack that are responsible for the reducing and stabilizing of AgNPs-PM. At concentrations ranging from 12.5 µg/ml to 400 µg/ml of AgNPs-PM, the percentage inhibition of cancer cells was insignificant, whereas 2 mg/ml AgNPs-PM tested on the microbial strains showed inhibition on their growth. Conclusion: AgNPs-PM has been successfully synthetised and characterised. However, the AgNPs possesses low bioactivities against bacterial and cytotoxic activities.